MORAL VALUES IN ENGLISH TEXTBOOK: “WHEN ENGLISH RINGS A BELL” - Sherina Kusramadhani; Rahmadi Nirwanto; Hesty Widiastuty (IKIP Siliwangi, 2022)
This research was aimed to know about moral values in the textbook. Textbooks were analyzed by using critical discourse analysis (CDA) data was obtained through analyzing the whole texts. This study attempts to examined the moral values which appeared in the English textbook